Repurposing of Anthocyanin Biosynthesis for Plant Transformation and Genome Editing - He, Yubing; Zhu, Min; Wu, Junhua; Ouyang, Lejun; Wang, Rongchen; Sun, Hui; Yan, Lang; Wang, Lihao; Xu, Meilian; Zhan, Huadong; Zhao, Yunde (Frontiers in Genome Editing, 2020)
CRISPR/Cas9 gene editing technology has been very effective in editing genes in many plant species including rice. Here we further improve the current CRISPR/Cas9 gene editing technology in both efficiency and time needed for isolation of transgene-free and target gene-edited plants. We coupled the CRISPR/Cas9 cassette with a unit that activates anthocyanin biosynthesis, providing a visible marker for detecting the presence of transgenes. The anthocyanin-marker assisted CRISPR (AAC) technology enables us to identify transgenic events even at calli stage, to select transformants with elevated Cas9 expression, and to identify transgene-free plants in the field. We used the AAC technology to edit LAZY1 and G1 and successfully generated many transgene-free and target gene-edited plants at T1 generation. The AAC technology greatly reduced the labor, time, and costs needed for editing target genes in rice.